Experimental and numerical investigation on the influence of a large crack on the modal behaviour of a Kaplan turbine blade. (January 2020) - Zhang, Ming; Valentin, David; Valero, Carme; Presas, Alexandre; Egusquiza, Mònica; Egusquiza, Eduard
Highlights: The influence on the modal behavior of a large crack in a Kaplan turbine has been studied. Experimental investigation on a cracked blade and on a non-damaged blade has been carried out. A numerical model to consider the non-linear effect of the crack has been implemented. The differences in natural frequencies due to the large crack have been analyzed. Mode shapes of Kaplan turbine blades with and without crack have been discussed. Abstract: A large crack was discovered on one blade of a Kaplan turbine prototype after the inspection of the machine. In order to know the origin of the crack, a failure analysis was previously carried out (Zhang et al., 2019). To know the modal behaviour of cracked structures is of interest in order to detect the crack while in operation. For this purpose, an experimental and numerical investigation of the damaged blade and of another non-damaged blade was performed. Results of natural frequencies and mode-shapes of both blades have been compared in order to identify the main differences in modal behaviour when a crack appears. The crack was so large than one part of the blade was deformed by its own weight, causing contact between the two surfaces of the crack. This fact gives an additional stiffness to the crack, which should be considered in the numerical models. For that, a stiffness change in this zone was included. The influence of this stiffness on the natural frequency values and mode-shapes has been studied in detail. In that way, a numerical model for estimating the modal behaviour of large cracks have been implemented and validated.